Inhibition of Biofilm Formation by T7 Bacteriophages Producing Quorum-Quenching Enzymes - Pei, Ruoting (American Society for Microbiology, 2014)
Bacterial growth in biofilms is the major cause of recalcitrant biofouling in industrial processes and of persistent infections in clinical settings. The use of bacteriophage treatment to lyse bacteria in biofilms has attracted growing interest. In particular, many natural or engineered phages produce depolymerases to degrade polysaccharides in the biofilm matrix and allow access to host bacteria. However, the phage-produced depolymerases are highly specific for only the host-derived polysaccharides and may have limited effects on natural multispecies biofilms. In this study, an engineered T7 bacteriophage was constructed to encode a lactonase enzyme with broad-range activity for quenching of quorum sensing, a form of bacterial cell-cell communication via small chemical molecules (acyl homoserine lactones [AHLs]) that is necessary for biofilm formation. Our results demonstrated that the engineered T7 phage expressed the AiiA lactonase to effectively degrade AHLs from many bacteria. Addition of the engineered T7 phage to mixed-species biofilms containing Pseudomonas aeruginosa and Escherichia coli resulted in inhibition of biofilm formation. Such quorum-quenching phages that can lyse host bacteria and express quorum-quenching enzymes to affect diverse bacteria in biofilm communities may become novel antifouling and antibiofilm agents in industrial and clinical settings.